2000
DOI: 10.1002/1097-4628(20001010)78:2<311::aid-app110>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Liquefaction and product identification of corn bran (CB) in phenol

Abstract: The liquefaction of corn bran (CB) was successfully conducted by using three different liquefaction conditions. Among them, catalyzed liquefaction at high pressure and temperature (180–220°C) using phenol was the most effective for the liquefaction of CB. Both the phenol/CB ratio and the catalyst content affected the extent of the liquefaction. The decomposed components of CB did not show high reactivity toward phenol when liquefied without a catalyst. Thermal‐flow properties of the phenolated CB and flexural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…It should, thus, be possible to decrease the cost of glucose and utilize it in industrial scale without consuming food resources. Polyols produced from wood flour cellulose [22], corn bran [23] and waste paper [24] have already been utilized to synthesize different polymers, mainly thermosets.…”
Section: Introductionmentioning
confidence: 99%
“…It should, thus, be possible to decrease the cost of glucose and utilize it in industrial scale without consuming food resources. Polyols produced from wood flour cellulose [22], corn bran [23] and waste paper [24] have already been utilized to synthesize different polymers, mainly thermosets.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained liquefied products were directly used to prepare polyurethane foam by reaction with diphenylmethane diisocyanate in the presence of catalyst, silicone surfactant, and water. Thermosetting moldings were prepared by hot-pressing the mixture of phenolated wood (37.7%), wood flour filler (49.5%), hexamine (9.4%), Ca(OH)2 (2.4%), and Zn stearate (1%) (Lee et al 2000b).…”
Section: Preparation Of Biomass-based Polymeric Materialsmentioning
confidence: 99%
“…These phenolic compounds from liquid products can be used as an important source of chemical intermediates. Numerous studies reported on the usage of the liquefied product from lignin to prepare phenol‐formaldehyde resin and polyurethane resin , . The incompletely carbonized solid product, i.e., hydrochar, from hydrothermal carbonization is also a kind of high‐available carbon source, which can be used as high‐energy solid fuel, precursor for preparation of activated carbon or carbon black, adsorbent, soil conditioner, etc.…”
Section: Introductionmentioning
confidence: 99%